Model of Using the Exhaustive Search Algorithm in Solving of Traveling Salesman Problem (TSP) on the Example of the Transport Network Optimization of Primorje-Gorski Kotar County (PGC) - Slavomir Vukmirović; Zvonko Čapko; Ana Babić (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
This paper considers and presents a model of the use of an exhaustive search algorithm in solving problems of a salesman on the example of the transportation network optimization of PrimorskoGoranska County. Visual and object oriented methods of modeling and programming in the design of the exhaustive search algorithm in the spreadsheet interface, enable calculating and finding the optimal solution of the transportation network, and also calculating the suboptimal solutions of transportation network with a clear interpretation of the results, both for the optimal value so for approximately equal value and their deviations from the optimal value. By identifying the suboptimal solutions of transportation network, that enable insight into more transportation routes and can be significantly influenced by the reduction of transportation costs and creating increased opportunities for the carrier in the context of flexible designing the structure of the commodity flows, greater utilization of transport capacity, and thus achieve greater profit. In the analyzed example, transportation network of Primorje-Gorski Kotar County (PGC) is divided into two sets (segment): 1) a set of cities (nodes) that are located (placed) on the same traffic direction (transportation route) that represents the optimal transportation route, and 2) a set of cities (nodes) that connect through a variety of transport relationships and that are included in the calculation by using the exhaustive search algorithm. In the example are also defined nodes that are common to both the two sets and that are connecting by the virtual transportation route in the spreadsheet optimization model.
Keywords: 650; Transportation networks; Travelling Salesman Problem; Primorje-Gorski Kotar County (PGC); Exhaustive Search Algorithm; optimal and suboptimal relationships; virtual transportation route